Comparative Study on the Effectiveness of Papaya Leaf (Carica papaya Linn) and Citrus Leaf (Citrus sp.) Infusions in Reducing Aedes aegypti Larvae Mortality - Ardian S Leky; Arif Andriyanto (Epidemiology and Society Health Review (ESHR), 2026)
Background: Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. Vector control efforts have thus far relied heavily on chemical larvicides, which can cause resistance and pollute the environment. This study aims to determine and compare the effectiveness of papaya leaf (Carica papaya Linn) and citrus leaf (Citrus sp.) infusions as natural larvicides against Aedes aegypti larvae. Method: This study was a laboratory experiment with a post-test-only control group design, using 150 Aedes aegypti instar III larvae divided into six test containers, each containing 25 larvae, with three replicates for papaya leaf infusion and three replicates for 40% concentrated citrus leaf infusion. The infusion was made from dried leaves, which were ground into powder, then boiled at 90°C for 15 minutes before being filtered. Each treatment was tested by adding 5 mL of infusion to a container containing 100 mL of water. The 24-hour mortality data were analyzed using a two-sample independent T-test or Mann–Whitney U test if the data were not normal, with a significance level of p < 0.05. Results: The results showed that there was a significant difference in larval mortality between papaya leaf infusion and citrus leaf infusion (p = 0.017). Citrus leaf infusion had a higher lethality rate than papaya leaf infusion. Citrus leaf infusion caused 100% larval mortality within 12 hours, while papaya leaf infusion showed an average mortality rate of 11.66 larvae within 24 hours. Conclusion: Infusions of citrus leaves and papaya leaves have been shown to have potential as natural larvicides against Aedes aegypti larvae. However, citrus leaf infusions are more effective.